Ecological Thresholds of Toxicological Concern: A Review - Barron, Mace G.; Otter, Ryan R.; Connors, Kristin A.; Kienzler, Aude; Embry, Michelle R. (Frontiers in Toxicology, 2021)
The ecological threshold of toxicological concern (ecoTTC) is analogous to traditional human health based TTCs but with derivation and application to ecological species. An ecoTTC is computed from the probability distribution of predicted no effect concentrations (PNECs) derived from either chronic or extrapolated acute toxicity data for toxicologically or chemically similar groups of chemicals. There has been increasing interest in using ecoTTCs in screening level environmental risk assessments and a computational platform has been developed for derivation with aquatic species toxicity data (https://envirotoxdatabase.org/). Current research and development areas include assessing mode of action-based chemical groupings, conservatism in estimated PNECs and ecoTTCs compared to existing regulatory values, and the influence of taxa composition in the distribution of PNEC values. The ecoTTC continues to develop as a valuable alternative strategy within the toolbox of traditional and new approach methods for ecological chemical assessment.